Regarding site cleaning, keeping healthy environment at the BRACU project site - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding site cleaning, keeping healthy environment at BRACU new campus project site.